REGULAR TRAINING COMBINED WITH E-CONTENT PACKAGES AND GAME-SPECIFIC DRILLS TO IMPROVE KABADDI SKILLS PERFORMANCE - V. Sundar; T. P. Yokesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Examining the impact of e-content-based coaching on specific Kabaddi skills was the aim of this study. Eighty male Kabaddi players, ages 18 to 25, were chosen as subjects from Alagappa University in Karaikudi in order to fulfil the study's objectives. With a pre-test and a post-test, the study was designed as a true random group design. Group I received instruction and coaching using an e-content package, Group II received instruction and coaching using a game-specific training, Group III received combined training, and Group IV received no training. The subjects were divided into four equal groups of twenty each at random. For twelve weeks, the experimental group followed their respective schedules on different days. Teaching & coaching session in the field lasted for 60 minutes. The chain tackle was assessed by subjective ratings. Analysis of covariance and scheffe’s method was used. It was found that the combined training package showed significant improvement on chain tackle than other experimental groups.